1999
DOI: 10.1080/j.1600-0412.1999.780902.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron status and iron balance during pregnancy. A critical reappraisal of iron supplementation

Abstract: In order to avoid iron deficiency in pregnancy, prophylactic iron supplement should be considered. Iron supplements may be administered on a general or selective basis. The selective approach implies screening with serum ferritin in early pregnancy, in order to identify women who can manage without prophylactic iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 35 publications
7
69
0
1
Order By: Relevance
“…All reviews concluded that iron supplementation increased haematological markers (haemoglobin or haematocrit), improved serum ferritin levels, and decreased the incidence of anaemia. Three reviews [27,32,33] (one high, one intermediate and one low quality) showed that such positive effects extended into the postnatal period, with improved maternal haemoglobin concentrations one month to eight weeks postpartum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All reviews concluded that iron supplementation increased haematological markers (haemoglobin or haematocrit), improved serum ferritin levels, and decreased the incidence of anaemia. Three reviews [27,32,33] (one high, one intermediate and one low quality) showed that such positive effects extended into the postnatal period, with improved maternal haemoglobin concentrations one month to eight weeks postpartum.…”
Section: Resultsmentioning
confidence: 99%
“…One systematic review of high quality [32] and one of low quality, [27] reported infant outcomes. In both, infants born to iron supplemented mothers had a higher serum ferritin at birth compared to non-supplemented women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious adverse effects are rare with iron sucrose, however minor side effects occur in up to 18% of patients which may in part be attributed to its non-physiological physical properties (high pH and high osmolarity). Ferric carboxymaltose is a newer dextran-free iron formulation with a near neutral pH, physiological osmolarity and increased bioavailability which allows for single dose, short 15 minute infusion time and higher dosing (up to 1000 mg) [17]. These properties make ferric carboxymaltose an attractive alternative to iron sucrose in terms of risk profile, efficacy, patient comfort and convenience, staff and institutional resource utilization.…”
Section: Introductionmentioning
confidence: 99%
“…The fetus is amazingly efficient at obtaining adequate iron from all but the most iron-deficient mother (20). There is no evidence that mild maternal anemia has adverse effects on the newborn.…”
Section: Maternal Anemia and Neonatal/childhood Outcomesmentioning
confidence: 99%